Evaluation of damage in giant cell arteritis. (3rd November 2017) - Kermani, Tanaz A; Sreih, Antoine G; Cuthbertson, David; Carette, Simon; Hoffman, Gary S; Khalidi, Nader A; Koening, Curry L; Langford, Carol A; McAlear, Carol A; Monach, Paul A; Moreland, Larry; Pagnoux, Christian; et al.
Abstract: Objectives: To evaluate damage and variables associated with damage in GCA. Methods: Patients with GCA enrolled in a prospective, multicentre, longitudinal study were included. Per-protocol assessments were made with the Vasculitis Damage Index and the Large-Vessel Vasculitis Index of Damage. Results: The study included 204 patients: 156 women (76%), mean age at diagnosis 71.3 years (s .d . 8.3), mean follow-up of 3.5 years (s .d . 1.9). One or more damage item was present in 54% at baseline and 79% at the last follow-up on the Vasculitis Damage Index, and 60% at baseline and 82% at the last follow-up on the Large-Vessel Vasculitis Index of Damage. The most frequently observed damage items were large-artery complications (29% cohort) and ocular (22%). Among 117 patients with new damage, most new items were ocular (63 patients), cardiac/vascular (48) and musculoskeletal (34). Of these, treatment-associated items were frequently observed, including cataracts (46 patients), osteoporosis (22) and weight gain (22). Disease-associated new damage included ischaemic optic neuropathy (3 patients), limb claudication (13), arterial occlusions (10) and damage requiring vascular intervention (10). In univariate analysis, the risk of damage increased 22% for every additional year of disease duration [odds ratio (OR) 1.22 (95% CI 1.04, 1.45)]. In 94 patients enrolled within ⩽90 days of diagnosis of GCA, the risk of new damage at the last follow-up decreased 30% for each additional relapse [OR 0.70 (95% CI 0.51, 0.97)]. Conclusions: Large-artery complications and ocular manifestations are the most commonly occurring items of damage in GCA. Most new damage is associated with treatment. These findings emphasize the cumulative burden of disease in GCA.